Mode of birth and women's psychological and physical wellbeing in the postnatal period - Rowlands Ingrid J; Redshaw Maggie (BMC, 2012)
Abstract Background Physical and psychological problems after childbirth are common, and may have a significant negative and long-term impact on women's wellbeing and daily functioning. The method of birth may be a particularly important factor influencing women's health and wellbeing following birth, however, population-wide evidence is limited. This study uses data from 5,332 women who responded to a national survey of women's experiences of maternity care in England. We examined women's postnatal wellbeing in the first three months after birth, and whether these varied by mode of birth. Methods This is a secondary analysis of survey data using a random sample of women selected from birth registration. We used multinomial logistic regression models to examine the association between women's self-reported psychological symptoms, health problems and mode of birth. Results Women who had forceps-assisted vaginal births and unplanned caesarean section births reported the poorest health and wellbeing, while those of women who had unassisted vaginal births and planned caesarean section births were less affected by the birth process. Most women's physical and emotional health appeared to improve with time, however, those who had a forceps-assisted vaginal birth were more likely to report ongoing posttraumatic-type symptoms several months after the birth. Conclusions Mode of birth was associated with differences in outcomes at three months. By comparison to women who had unassisted vaginal births, the risk of reduced postnatal health and wellbeing was higher amongst the women who had forceps-assisted vaginal births but not amongst women who had ventouse-assisted vaginal births. This would suggest that it is important to differentiate the different types of instrumental birth in outcome studies. Of concern was the higher rate of posttraumatic-type symptoms among women who had forceps-assisted vaginal births relative to the other modes of birth. Women who have forceps-assisted births should be monitored carefully by health professionals in the postnatal period, and in the months after childbirth, when they could be offered the opportunity to discuss their labour and birth.